2021
DOI: 10.3389/fvets.2021.727155
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Myocardial Adaptation Assessed by Two-Dimensional Speckle Tracking Echocardiography in Canine Models of Chronic Pulmonary Hypertension

Abstract: Background: Pulmonary hypertension (PH) is a life-threatening disease in dogs characterized by an increase in pulmonary arterial pressure (PAP) and/or pulmonary vascular resistance. Right ventricle adapts to its pressure overload through various right ventricular (RV) compensative mechanisms: adaptive and maladaptive remodeling. The former is characterized by concentric hypertrophy and increased compensatory myocardial contractility, whereas the latter is distinguished by eccentric hypertrophy associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…Although TR velocity showed the same tendency as PVRecho, a previous study has reported that systolic PAP estimated by TR velocity showed poor agreement with that measured by catheterization ( 31 ), and ACVIM consensus stated that PH diagnosis by TR velocity alone should be avoided ( 1 ). Furthermore, our previous study reported that RV compensated for mild pressure overload by hyperactivation and decompensated for moderate-to-severe and chronic pressure overload in dogs with experimentally induced PH ( 27 ), suggesting that the pseudo-normalization of RV systolic function cannot be avoided as PH progresses. Therefore, the overall assessment of RV performance and afterload, such as PVRecho and PVRecho2, might be more useful for the clinical assessment of PH rather than the assessment using TR velocity and/or RV performance variables alone.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although TR velocity showed the same tendency as PVRecho, a previous study has reported that systolic PAP estimated by TR velocity showed poor agreement with that measured by catheterization ( 31 ), and ACVIM consensus stated that PH diagnosis by TR velocity alone should be avoided ( 1 ). Furthermore, our previous study reported that RV compensated for mild pressure overload by hyperactivation and decompensated for moderate-to-severe and chronic pressure overload in dogs with experimentally induced PH ( 27 ), suggesting that the pseudo-normalization of RV systolic function cannot be avoided as PH progresses. Therefore, the overall assessment of RV performance and afterload, such as PVRecho and PVRecho2, might be more useful for the clinical assessment of PH rather than the assessment using TR velocity and/or RV performance variables alone.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an increased RVIDd index was also associated with the presence of R-CHF with high AUC, sensitivity, and specificity, as well as PVRecho2. We previously described RV maladaptation against RV afterload in dogs with chronic PH and that RV dysfunction would induce RV dilatation to maintain RV cardiac output ( 27 ). Dogs with R-CHF in this study also showed RV dysfunction based on a decrease in RV-SL and RV-SrL and increased RV afterload based on TR velocity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations